Concurrent and Longitudinal Relationships Between Development in Graphic, Language and Symbolic Play Domains from the Fourth to the Fifth Year. Issue 3 (27th November 2012) - Kirkham, Julie; Stewart, Andrew; Kidd, Evan
<x xml:space="preserve">Abstract</x> This research investigated the developing inter‐relationships between language, graphic symbolism and symbolic play both concurrently and longitudinally from the fourth to the fifth year of childhood. Sixty children (n = 60) aged between 3 and 4 years completed multiple assessments of language and assessments of graphic symbolism, symbolic play and non‐verbal intelligence. A year later, 31 children (n = 31) were re‐tested using the same assessments. The findings revealed that skills within each symbolic domain were inter‐related during the fourth year, appearing to develop in a domain‐general type fashion based upon a common underlying symbolic mechanism. However, between the fourth and the fifth years, only language had predictive validity, suggesting a shift towards the verbal mediation of symbolic play and graphic symbolism as language becomes progressively internalized (Vygotsky, 1962, 1978). Copyright © 2012 John Wiley & Sons, Ltd.